2022
DOI: 10.1200/op.22.00385
|View full text |Cite
|
Sign up to set email alerts
|

Treating Smoking in Cancer Patients: An Essential Component of Cancer Care—The New National Cancer Institute Tobacco Control Monograph

Abstract: PURPOSE: Continued smoking after the diagnosis of cancer can markedly worsen oncology treatment side effects, cancer outcomes, cancer mortality, and all-cause mortality. Conversely, mounting evidence demonstrates that smoking cessation by patients with cancer improves outcomes. A cancer diagnosis often serves as a teachable moment, characterized by high motivation to quit. However, too few patients with cancer who smoke are offered evidence-based smoking cessation treatment, and too few engage in such treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These findings suggest that a standardized tobacco use assessment with opt-out referral to tobacco treatment in a large cancer care setting is feasible and achieves higher tobacco treatment referral and acceptance rates than typically observed . By normalizing tobacco use screening and treatment as essential elements of high-quality cancer care, a universal tobacco screening and opt-out referral strategy may mitigate the stigma associated with patient engagement in tobacco treatment . An opt-out referral model may eliminate clinician referral bias and thereby facilitate equitable access to and use of tobacco treatment services among racially and ethnically diverse patients with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that a standardized tobacco use assessment with opt-out referral to tobacco treatment in a large cancer care setting is feasible and achieves higher tobacco treatment referral and acceptance rates than typically observed . By normalizing tobacco use screening and treatment as essential elements of high-quality cancer care, a universal tobacco screening and opt-out referral strategy may mitigate the stigma associated with patient engagement in tobacco treatment . An opt-out referral model may eliminate clinician referral bias and thereby facilitate equitable access to and use of tobacco treatment services among racially and ethnically diverse patients with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Tobacco use, which is more common among males than females, might explain the poorer survival observed among males with stomach or lung cancer. 26 Differences in cancer survival by ethnicity in Zimbabwe could be explained by the fact that the follow-up of registered cancer cases in Harare showed that many hospital admissions among the white population were to the private sector, with probable better access to care.…”
Section: Discussionmentioning
confidence: 99%
“…Continued smoking after a cancer diagnosis has been linked with shorter survival, recurrent disease, decreased treatment efficacy, and reduced quality of life [1]. In the United States (US) and other high-income countries, a cancer diagnosis has been used as a window of opportunity to intervene and provide smoking prevention and cessation assistance to patients and survivors [2,3]. Findings from Irene Tamí-Maury and Samuel Tundealao are joint first authors and contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%